Riesgos y beneficios del sistema de aspiración traqueal cerrado y abierto en la unidad de cuidados intensivos - Pucha Quichimbo, Daysi Graciela (2025)
In the context of the intensive care unit, nursing professionals must have the appropriate training to carry out a conglomerate of rigorous procedures, one of these being the aspiration of tracheal secretions. The objective of this work was to identify the risks and benefits that affect the closed and open tracheal aspiration system in the intensive care unit through a bibliographic review. This was a documentary, qualitative, descriptive, cross-sectional, and non-experimental study. University databases and repositories were reviewed. The initial search allowed 178 documents to be identified. Using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses method, 25 articles were selected and included in the review. The findings of the article suggest that the main risks of the open tracheal aspiration system derive from the disconnection of the ventilation system, leading to hemodynamic imbalance; these include the possibility of carrying out the removal of secretions more effectively. However, the risks of the closed tracheal suction system include increased microbial colonization and risk of infection. The benefits of this type of circuit include the possibility of performing suction multiple times, no disconnection required, and lower cost. In conclusion, the closed tracheal suction system reduces the risk of infection, multi-organ failure, and death, with shorter ventilation time and hospital stay, but presents greater bacterial proliferation and less secretion clearance. The open system improves the removal of secretions, but with greater hemodynamic instability and pain.